Antioxidant And Antifungal Activities Of Several Malaysian Wood Extracts - Shaharuddin, Nurul Atiqah (2012)
Antioxidant activities, antifungal properties and total phenolic compound of 11 selected commercial Malaysian timbers were studied. The species include Syzygium samarangense (kelat jambu air), Eugenia cerina (kelat gelam), Eugenia chorantha (kelat merah), Scorodocarpus borneensis (kulim), Myristica cinnamomea (penarahan arang), Artocarpus elasticus (terap nasi), Pometia pinnata (kasai daun besar), Palaquium hispidum (nyatoh tembaga kuning), Casuarina equisetifolia (rhu), Azadirachta indica (neem) and Gonystylus bancanus (ramin melawis). Extract from bark, sapwood and heartwood of each species were screened for antioxidant using 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay for antioxidant activities, whereas the total phenolic compound was evaluated using the Folin-Ciocalteu method. The antifungal activities were observed with Gloephyllum trabeum (brown-rot) and Pycnoporus sanguineus, which is white-rot. Eugenia cerina (Kelat gelam) bark showed the highest antioxidant activity while the highest total phenol content was found in Azadirachta indica (neem) bark.